Relationship between learning style and academic performance of accounting undergraduates in online classes / Nur Syazwani Mohammad Fadzillah ...[et al.] - Mohammad Fadzillah, Nur Syazwani; Ahmad, Mohamad Azmi Nias; Jamaluddin, Junaidah; Mohd Din, Norlaila; Abdul Jabar, Faizan (Universiti Teknologi MARA Cawangan Pahang, 2021)
Learning style refers to learners' favoured approach to learning, which includes the process of receiving, collecting, processing, and interpreting to become knowledgeable. There are different learning styles. Three of the most popular ones are visual, auditory, and kinaesthetic. This study aims to investigate the effect of different learning styles on academic performance of students and relationship between learning styles and academic performance of students in online classes. A sample of 94 accounting undergraduates was selected for the study. Findings of the study revealed that, visual learning style was found to be more prevalent than auditory and kinaesthetic learning styles. There was no significant effect of learning style on students' academic performance in online classes. Besides that, there was also a very low negative relationship between learning style and students' academic performance in online classes.